Analisis Kinerja Penyuluh Keluarga Berencana Kota Palembang - Kurniati, Aria (Direktorat Riset dan Pengabdian Kepada Masyarakat Universitas Bina Darma, 2019)
This research was conducted with the aim to analyze the performance of family planning counselors Palembang city. In this study, the authors used a qualitative descriptive approach that explains the phenomenon in depth about the performance of family planning counselors Palembang city. To use primary data, researchers used several data collection techniques, namely through observation and interviews. Observation In this case the researcher directly observes the performance of family planning counselors and the behavior of people who are still Fertile Age Couples. Interviews were conducted with informants namely Head of Subdivision Relations between institutions and field lines, Family Planning counselors Palembang city and people who are still fertile age couples. Based on the results of the analysis and discussion it can be concluded that the performance of family planning counselors is quite good but there are some that have not been maximized. This can be seen from the number of performances that are not comparable with the number of target villages, which are 48 instructors who guide 107 villages. Submission of information or counseling from family planning counselors has not been effective because of the limited number of extension workers besides that the community is also more confident and trusting in health workers than family planning counselors. Some people know information about family planning from midwives at Posyandu or Puskesmas. The task of extension agents for the position of extension agents or group IV is still not in accordance with the conditions in the field because their occupation is already provincial level, but in reality they are still working in the village area. Levels of education from various disciplines and there are still a number of high school graduates who influence the message or counseling that will be delivered. And the quota provided in education and technical training for extension workers is still limited.